2015
DOI: 10.1063/1.4913673
|View full text |Cite
|
Sign up to set email alerts
|

Study of the shock wave structure by regularized Grad’s set of equations

Abstract: In this work, we continue to study the possibility of applying moment equations for strongly nonequilibrium flows by an example of the problem of the shock wave structure in a monatomic gas in a wide range of Mach numbers for various models of molecular interaction. The object of the study is the so-called regularized 13-moment Grad's system (R13). First time, both linear and nonlinear versions of this system of equations were considered for the problem at such wide range of parameters. The Godunov method with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The terms omitted in the linear case form the so-called non-gradient transport mechanisms (NGTM) [5]. The linear variant (10) and the original nonlinear variant (7)-(9) were studied for shock structures in [6][7][8].…”
Section: Original Variant (2003)mentioning
confidence: 99%
“…The terms omitted in the linear case form the so-called non-gradient transport mechanisms (NGTM) [5]. The linear variant (10) and the original nonlinear variant (7)-(9) were studied for shock structures in [6][7][8].…”
Section: Original Variant (2003)mentioning
confidence: 99%
“…The existence of this peak predicted by approximate analytical methods by several researchers, e.g., [14], is questioned in [1]. However, the overshoot was obtained in DSMC computations (see, e.g., [16][17][18][19]). Unfortunately, at the moment the existence of this peak cannot be confirmed by experiments because of the lack of temperature data at high Mach numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The variant of high resolution Godunov scheme with linear flow parameter reconstruction is chosen for numerical solution of the R13 set of equations [21]. The second-order accuracy in space for smooth solutions is achieved using essentially two-dimensional reconstruction procedures [12,21] for the primitive variables within each computational cell. The standard central difference approximation is used for elliptical part discretization of the fluxes (diffusion terms).…”
Section: Methodsmentioning
confidence: 99%
“…The difference between them lies in the relations for higher order moments [8,9]. It has been shown that all variants are well applicable for numerical modelling of the moderately rarefied slow gas flows and allow the modelling of main nonequilibrium effects in low-velocity micro-flow problems [10,11,12,13,14,15,16,17] and some moderately rarefacted supersonic flows [5,18,19,15,20,21,22]. The difficulty is that the solid wall boundary conditions for R13 equations were obtained from one of the variants [10] which is not applicable to near hypersonic flows [9].…”
Section: Introductionmentioning
confidence: 99%